Tirantes: de palco dos criativos a cidade criativa: caminho possível? - Oliveira, Juliana Minardi de (2015)
This study aims to contribute to the development of the municipal tourism policy in Tiradentes, municipality from the state of Minas Gerais, Brazil.Socioeconomic and demographic analysis are performed. The development from production and labour market of tourism and creative market are investigated, also themunicipal planning and management of tourism and culture were studied. Intends to understand the use and occupation of the territory and identify potentials, particularly those related to creative city concepts and creative economy, examining signs and possible paths to a more participatory, inclusive and democratic development for this municipality. It was identified that Tiradentes has elements of the first stage of transformation of an ordinary city into a creative city (state of latency). There is potential in the creative segments of Audiovisual, Design, Cultural Expressions, Fashion and Heritage and Arts. In conclusion, an effort of integrated and participatory planning for the city's development should be continued, considering the creative sectors for which the city is vocationed, which can enable an advance of it to new stages which promote socio-economic development in a more inclusive and sustainable way, through the creative economy and tourism.